Btbd8 deficiency reduces susceptibility to colitis by enhancing intestinal barrier function and suppressing inflammation - Yang, Xiaoqiong; He, Zichan; Dong, Qiman; Nai, Shanshan; Duan, Xiaowei; Yu, Jiayu; Zhao, Nannan; Du, Xiaoling; Chen, Lingyi (Frontiers in Immunology, 2024)
BTBD8 has been identified as a susceptible gene for inflammatory bowel diseases (IBD). However, the function of BTBD8 in normal development and IBD pathogenesis remains unknown. Here, we demonstrated that Btbd8 deficiency partially protects mice from dextran sodium sulfate (DSS)induced IBD, even though no obvious phenotypes were observed in Btbd8 knockout (KO) mice. Btbd8 deletion leads to strengthened tight junctions between intestinal epithelial cells, elevated intestinal stem cell activity, and enhanced mucus layer. All these three mechanisms work together to improve the intestinal barrier integrity in Btbd8 KO mice. In addition, Btbd8 deficiency mitigates inflammation by reducing the expression of IL-1β and IL-6 by macrophages. In conclusion, our studies validate the crucial role of Btbd8 in IBD pathogenesis, and reveal that Btbd8 deficiency may ameliorate DSS-induced IBD through improving the intestinal barrier integrity, as well as suppressing inflammatory response mediated by macrophages.